2017
DOI: 10.1021/acsami.7b09807
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Nonlinear Optical Visibility of Two-Dimensional Materials

Abstract: Two-dimensional (2D) materials have attracted broad research interests across various nonlinear optical (NLO) studies, including nonlinear photoluminescence (NPL), second harmonic generation (SHG), transient absorption (TA), and so forth. These studies have unveiled important features and information of 2D materials, such as in grain boundaries, defects, and crystal orientations. However, as most research studies focused on the intrinsic NLO processes, little attention has been paid to the substrates underneat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…The third factor is the substrate effect. Xianchong et al reported that SHG intensity can be increased about 100‐fold by varying the SiO 2 thickness of the SiO 2 /Si substrate, which was attributed to the constructive interference effect . Another important reason is the excitonic effects.…”
Section: Nlo Processes In Tmdsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third factor is the substrate effect. Xianchong et al reported that SHG intensity can be increased about 100‐fold by varying the SiO 2 thickness of the SiO 2 /Si substrate, which was attributed to the constructive interference effect . Another important reason is the excitonic effects.…”
Section: Nlo Processes In Tmdsmentioning
confidence: 99%
“…Xianchong et al reported that SHG intensity can be increased about 100-fold by varying the SiO 2 thickness of the SiO 2 /Si substrate, which was attributed to the constructive interference effect. 72 Another important reason is the excitonic effects. There were numerous papers reported that SHG could be enhanced dramatically when the excitation laser was in resonance with the excitonic peak.…”
Section: Second-harmonic Generationmentioning
confidence: 99%
“…[ 39,40 ] The higher conversion efficiency in NLO material can be enhanced by the use of the MoS 2 3R phase. To increase the 2DLMs SHG interaction power by optical techniques like interference, [ 41,42 ] wave‐guides, [ 43 ] and cavities, [ 44,45 ] can be adopted. The 2D based TMDCs non‐centrosymmetric materials make them auspicious candidates for ultra‐compact light highly efficient conversion photonic based nanodevices.…”
Section: Basic Techniques To Characterize Nonlinear Optics Of 2d Materialsmentioning
confidence: 99%
“…On the other hand, a direct calibration using an estimated incident intensity at the beam waist was also proposed to derive the TMD susceptibility [10][11][12], but this approach appears to be delicate due to very precise identification of all beam parameters that must be integrated. The effect of the substrate can also strongly modify the emitted SH signal due to additional interference contributions [12,13], and strain artifacts are known to result in SHG variations [14]. In terms of TMD materials, a few studies have highlighted the effect of crystalline quality on discrepancies between the published χ (2) values between mechanically exfoliated samples and those obtained from chemical vapor deposition (CVD) [10,15].…”
Section: Introductionmentioning
confidence: 99%